2020
DOI: 10.1109/tbme.2019.2935229
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Tracking Multiple Implanted Magnets With a Myokinetic Control Interface: Simulation and Experimental Evidence Based on the Point Dipole Model

Abstract: The quest for an intuitive and physiologically appropriate human-machine interface for the control of dexterous prostheses is far from being completed. To control a hand prosthesis, a possible approach could consist in using information related to the displacement of forearm muscles of an amputee during contraction. We recently proposed that muscle displacement could be monitored by implanting passive magnetic markers (MMsi.e. permanent magnets) in them. We dubbed this the myokinetic interface. However, beside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 36 publications
3
34
1
Order By: Relevance
“…In the following works [ 150 , 151 ], researchers assessed the accuracy of the position tracking of multiple magnetic markers with a set of magnetic field sensors. It was found that increasing number of magnets (and decreasing available space between them) causes localization errors and false predictions to occur more often.…”
Section: Promising Control Approachesmentioning
confidence: 99%
“…In the following works [ 150 , 151 ], researchers assessed the accuracy of the position tracking of multiple magnetic markers with a set of magnetic field sensors. It was found that increasing number of magnets (and decreasing available space between them) causes localization errors and false predictions to occur more often.…”
Section: Promising Control Approachesmentioning
confidence: 99%
“…Then, a sensor selection strategy (described in the next section) was implemented, aiming at reducing the computational complexity of the localization problem, while still ensuring adequate accuracy. Likewise, the algorithm approximated the MMs as point-like dipoles for solving the localization problem, akin to several previous works [12], [14]. The localization error, both in terms of position and orientation, was assessed relatively to the starting position as:…”
Section: Localization Problemmentioning
confidence: 99%
“…A few exceptions to single marker systems are the trackers developed by Yang et al [12], Taylor at al. [13] and Tarantino et al [14] that considered the pose of three (15 unknowns), four (20 unknowns) or seven (35 unknowns) markers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations